Molecular Analysis of Burkholderia cepacia Complex Isolates from a Portuguese Cystic Fibrosis Center: a 7-Year Study - Cunha, Mónica V. (American Society for Microbiology, 2003)
This work reports results of a systematic molecular analysis involving 113 Burkholderia cepacia complex isolates obtained from 23 cystic fibrosis (CF) patients under surveillance over a 7-year period at the major Portuguese CF center, the Santa Maria Hospital in Lisbon. The majority of the isolates were serial isolates from persistently infected patients (more than one-half of the population examined). In agreement with previous studies, B. cenocepacia (formerly genomovar III) was the most prevalent species; it was isolated from 52% of the patients infected with B. cepacia complex isolates. Contrasting with previous studies, a very significant percentage of the Portuguese CF subpopulation examined was infected with B. cepacia genomovar I (36%) and B. stabilis (18%). B. multivorans was recovered from two of the infected patients. All four of the species or genomovars were associated with poor clinical outcome, including the cepacia syndrome, and gave rise to chronic and transient infections, with the clinical condition depending on the patient and other still-unidentified factors. The B. cepacia epidemic strain marker region was found exclusively in genomovar III strains, while cblA was detected in genomovars I and III, only. There was no clear relation between the presence of these markers and transmissibility. Altogether, our results indicate that the use of these markers or the genomovar status in identifying patients at higher risk for infection is uncertain.